Air traffic controllers strike case: broke of consensus - Jesus, Samuel de (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2013)
The case study of air traffic controllers allows to discussion about new functions enlargement that has been tearing with that long-lived exercised through industry workers, now named non-industrial activities. This paper list the main discussions among authors mentioned about capitalism production system and seeks to settle possible links with air traffic controllers that involves precariousness, long work journeys they are submitted, short salaries and even the terrible condition of their work equipment. The air traffic controllers function could be an analyze object beneath light of work studies.